Ahmad Ibrahim and the Islamization of law in Malaysia - amir, ahmad nabil (Program Pascasarjana UIN Sumatera Utara Medan, 2025)
This article aims to explore the work and contribution of Ahmad Ibrahim (1916-1999) in his effort to Islamize law in Malaysia. It discusses in depth his method to apply Islamic law as set forth in his works and the consistent effort in striving to espouse and bring about harmonization of Islamic and civil law of the British colonies. The study is based on qualitative method using primary and secondary sources. The data was systematically analyzed in a descriptive, historical and comparative manner. The finding shows that Ahmad Ibrahim has bring about unprecedented reform in the administration of Islamic law in Malaysia and espoused instructive ways for the realization of the maqasid and shariahization spirit in contemporary context. He had constructed and formulated comprehensive and unprecedented structure of instructive and highly possible method to Islamize law and to bring about harmonization of Islam and civil law in Malaya by espousing for independent legal and criminal administration of Islamic law and formation of the highly anticipated Shariah court in Malaya.